Mechanical stimulation of the scalp improves the extra- and intracranial blood circulation in humans and mice - Yan Tan; Fang He; Ce Zhang; Jiani Zhang; Ziwei Chen; Xu Wang; Peng Wei; Yinan Nan; Louis Lei Jin; Qian Hua (Journal of Traditional Chinese Medical Sciences, 2020)
Background: Scalp combing, as an ancient method of health care, has been used for thousands of years in traditional Chinese medicine. Although this method is considered to be beneficial for the blood circulation of the head, the underlying mechanisms remain unclear. Methods: Both human participants and mice were used in this study. In participants, the scalp was stimulated by combing continuously for 5 min, and the temperature was measured using infrared thermal imaging before and after stimulation. In mice, the temperature was determined before and at 5, 15, and 30 min after a 5-min scalp mechanical stimulation (SMS). Additionally, the vasculature of the mice was labeled with retro-orbital fluorescein isothiocyanate-dextran injection, and the capillaries were observed directly under a confocal microscope. Using in vivo CLARITY imaging and the spectrofluorometric detection of Evans Blue dye extravasation, the blood–brain barrier permeability was assessed. Results: SMS increased the temperature of the left ear significantly in human (P = .0247) while can slightly increase the temperature of the right ear and the face without significant difference (P > .05). Moreover, SMS can significantly slow the decrease in the temperature of the external auditory canal at 5 min (P = .0153) and in body temperature at 15 min (P = .0295) after SMS whereas no significant difference in body temperature at 30 min (P > .05) compared with control mice. Furthermore, capillaries of the ear with a diameter of less than 8 μm were significantly dilated (P = .0006) following SMS and the number of dextran dots was higher at 15 min (P > .05) and 30 min (F = 10.98, P = .037) after SMS intervention compared with control mice. Conclusion: Our study provides strong evidence to support the notion that scalp combing can improve extra- and intracranial blood circulation under healthy conditions.